Trimming, Miniaturization and Ideality via Convolution Technique of TRIZ A Guide to Lean and High-level Inventive Design - Kwatra, Saurabh. (SpringerBriefs in Applied Sciences and Technology, 2013)
The book is a valuable research tool-kit for innovators, amateur & professionals alike. Additionally, College & University faculties on Engineering, who organize yearly workshops internationally will find hundreds of novel themes to choose from. Some teachers might just secretly buy this book to introduce out-of-box brain-teasers in classroom to add fizz to normal (at times boring) lecturing. The book can be used as main/add-on textbook towards following courses: (1) Master's degree programs on design innovation worldwide and (2) Senior undergraduate courses in industrial, engineering & product design.